Optoelectronics and photonics principles and practices - Kasap, S. O. (Safa O.) (Pearson Education Limited, 2013)
This text takes a fresh look at the enormous developments in electo-optic devices and associated materials-such as Pockels (Lithium Niobate) modulators.